GCK inhibition enhances iberdomide antimyeloma effects by promoting IKZF1 degradation via a CRBN-independent mechanism - Shirong Li; Josefine Krüger; Guifen Liu; Huihui Ma; Michael S. Hughes; Rajshekhar Chakraborty; Divaya Bhutani; Markus Y. Mapara; Christophe Marcireau; Suzanne Lentzsch; Jing Fu (Blood Neoplasia, 2025)
Abstract: Our recent study identifies germinal center kinase (GCK) as a novel therapeutic target in RAS-mutated multiple myeloma (MM). Inhibiting GCK downregulates critical transcriptional factors, notably IKZF1/3, BCL-6, and c-MYC proteins, leading to MM cell growth inhibition and cell death. Distinct from immunomodulatory drug (IMiD)–induced IKZF1/3 degradation, GCK inhibition triggers IKZF1/3 proteolysis through a cereblon (CRBN) E3 ligase–independent mechanism. Here, we demonstrated that GCK inhibition overcomes IMiD resistance in MM. An isogenic subline of MM.1S cells with acquired lenalidomide resistance remains sensitive to GCK inhibition–induced IKZF1/3 downregulation and cell growth inhibition. Consistently, the CRBN-resistant IKZF1 Q146H mutant maintains sensitivity to GCK inhibitor–induced degradation, similar to the IKZF1 wild-type protein, suggesting a CRBN-independent protein degradation. In accordance with the distinct IKZF1/3 degradation mechanisms, GCK silencing enhances iberdomide-induced IKZF1/3 and c-MYC downregulation and MM growth inhibition. More importantly, the combination of a GCK inhibitor with iberdomide exhibited synergistic anti-MM effects in a panel of MM cell lines and primary plasma cells. The synergistic effects were confirmed in an MM xenograft mouse model, in which combining GCK silencing and iberdomide resulted in significantly enhanced tumor inhibition and prolonged mice survival compared to single treatments. These findings underscore GCK as a promising therapeutic target for bypassing IMiD resistance in MM. Combining GCK inhibition with iberdomide could provide a novel strategy to manage relapsed or refractory patients with multidrug resistance, especially after the exhaustion of immunotherapy.